Protein Nanoparticles for Intracellular Delivery of Therapeutic Enzymes. Issue 6 (16th April 2014) - Estrada, Lina Herrera; Chu, Stanley; Champion, Julie A.
<x xml:space="preserve">Abstract</x> The use of enzymes as therapeutics is very promising because of their catalytic activity and specificity. However, intracellular delivery of active enzymes is challenging due to their low stability and large size. The production of protein‐enzyme nanoparticles was investigated with the goal of developing a protein carrier for active enzyme delivery. β‐Galactosidase (β‐gal), an enzyme whose deficiency is the cause of some lysosomal storage disorders, was incorporated into enhanced green fluorescent protein nanoparticles prepared via desolvation. Particle size was found to be sensitive to the type of cross‐linker, cross‐linking time, and the presence of imidazole. The results indicate that β‐gal activity is highly retained (>70%) after particle fabrication and >85% of protein is incorporated in the particles. Protein‐enzyme nanoparticles exhibited higher internalization in multiple cell lines in vitro, compared with the soluble enzyme. Importantly, β‐gal retained its activity following intracellular delivery. These data demonstrate that protein nanoparticles are a biocompatible, high‐efficiency alternative for intracellular delivery of active enzyme therapeutics. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci